Increasing Youth Capacity Through Language Workshops and Agricultural Business Skills to Increase Family Income - Amron Zarkasih Ritonga; Maimunah Ritonga; Joni Rianto; Rini Antika Ritonga (Asskruie: Jurnal Pengabdian Kepada Masyarakat, 2024)
The program "Increasing Youth Capacity Through Language Workshops and Agricultural Business Skills to Increase Family Income" aims to increase youth interest in the agricultural sector and equip them with the business skills necessary to be successful in this field. This program includes intensive training that combines theory and practice, covering modern agricultural techniques, business management, digital marketing, and product promotion. By providing access to quality training and continuing education, this program ensures that participants gain knowledge and skills that are relevant and ready to be applied in partner businesses. The program results showed a significant increase in youth interest in agriculture, which was achieved through providing information about the potential and business opportunities in this sector as well as practical experience in the field. In addition, participants' business promotion abilities are improved through training in digital marketing strategies and creating attractive promotional materials. Discussions and sharing of experiences during the workshop also provided creative ideas and practical solutions that can be implemented in partner businesses. Overall, this program has had a positive impact in increasing the capacity and skills of youth in the agricultural sector. It is hoped that with continued support, these young people can contribute more to increasing family income and the welfare of their community. This program shows that comprehensive and sustainable training can be the key to empowering youth and developing the agricultural sector